1977
DOI: 10.1002/cne.901720409
|View full text |Cite
|
Sign up to set email alerts
|

Projections from the amygdaloid complex and adjacent olfactory structures to the entorhinal cortex and to the subiculum in the rat and cat

Abstract: Axonal projections are described from the lateral and basolateral nuclei of the amygdaloid complex, and from the overlying periamygdaloid and prepiriform cortices and the endopiriform nucleus, to the lateral entohinal area, the ventral part of the subiculum, and the parasubiculum in the cat and rat. All of these projections have well-defined laminar patterns of termination, which are complementary to those of other projections to the same structure. Based on these results, and on cytoarchitectonic distinctions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
181
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(198 citation statements)
references
References 39 publications
16
181
1
Order By: Relevance
“…These observations are congruent with previous findings that amygdalar lesions block or attenuate a range of stress-induced effects such as LTP and spatial memory , gastric erosion (Henke, 1981), and analgesia (Helmstetter, 1992). Anatomically, the amygdala sends direct (from the magnocellular and parvicellular divisions of the basolateral amygdala to the CA1 and subiculum) and indirect (via the entorhinal cortex) projections to the hippocampus (Krettek and Price, 1977;Aggleton, 1986;Pikkarainen et al, 1999), routes by which it can influence hippocampal functions (Kim and Diamond, 2002). Because muscimol increases Cl Ϫ ion conductance across cell membranes (Feldman et al, 1997), the drug effects presumably are caused by inhibition of amygdalo-hippocampal activity during stress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These observations are congruent with previous findings that amygdalar lesions block or attenuate a range of stress-induced effects such as LTP and spatial memory , gastric erosion (Henke, 1981), and analgesia (Helmstetter, 1992). Anatomically, the amygdala sends direct (from the magnocellular and parvicellular divisions of the basolateral amygdala to the CA1 and subiculum) and indirect (via the entorhinal cortex) projections to the hippocampus (Krettek and Price, 1977;Aggleton, 1986;Pikkarainen et al, 1999), routes by which it can influence hippocampal functions (Kim and Diamond, 2002). Because muscimol increases Cl Ϫ ion conductance across cell membranes (Feldman et al, 1997), the drug effects presumably are caused by inhibition of amygdalo-hippocampal activity during stress.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, amygdalar lesions, stimulations, and drug infusions have been reported to modulate the magnitude of DG LTP (Abe, 2001). These findings suggest that the amygdala, via its projection to the hippocampus (Krettek and Price, 1977;Pikkarainen et al, 1999), might be involved in mediating stress effects on hippocampal functioning. In support of this notion, electrolytic lesions of the amygdala before stress have been found to prevent stress effects on LTP and spatial memory in rats ; however, because electrolytic lesions damage both cells and fibers of passage, it is unclear whether the lesion effects were resulting from damaging amygdalar neurons or fibers that course through the amygdala.…”
Section: Introductionmentioning
confidence: 95%
“…The insula receives input from the basolateral amygdala (Krettek and Price, 1977;Shinonaga et al, 1994) and projects to the striatum (Wright and Groenewegan, 1996) and is thus is considered an integral part of the corticomesolimbic system. The insula is hypothesized to mediate higher cognitive processes such as memory and learning related to taste (Balleine and Dickinson, 2000;Braun et al, 1972;Kiefer and Braun, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…A monosynaptic connection between the amygdala and hippocampus has been described only for projections to the temporal aspect of CA1 near the subiculum. In the rat, the amygdala projects to ventral subiculum, parasubiculum and lateral entorhinal cortex (Krettek and Price, 1977). Furthermore, (Kajiwara et al, 2003) have shown that amygdalar stimulation promotes the spread of excitatory neural activity from perirhinal cortex to the entorhinal-hippocampal circuit (the hippocampal formation circuitry is extensively reviewed in (Schwartzkroin and McIntyre, 1997;Witter and Amaral, 2004)).…”
Section: Discussionmentioning
confidence: 99%